Uric acid and skeletal muscle status in females with rheumatoid arthritis - Olga V. Dobrovolskaya; Maria V. Kozyreva; Nikolay V. Demin; Natalia V. Toroptsova (Терапевтический архив)
Aim. To study the association of uric acid (UA) levels with skeletal muscle mass, strength and physical performance in women with rheumatoid arthritis (RA).